Exploring The Use of Singing and Action Songs in Early Childhood English Vocabulary Learning - Rahmaniar; Sri Yulanda kadir (Synergy Education Journal of Multidisciplinary Language and Social Sciences, 2026)
This study aims to examine the influence of singing and action songs on improving English vocabulary mastery among early childhood learners through a literature study approach. Vocabulary acquisition is a fundamental component of language skills, particularly for children aged 4–6 years who are experiencing rapid development in both receptive and productive language abilities. In early childhood education, learning methods that are enjoyable, interactive, and developmentally appropriate are essential. Singing and action songs are considered effective strategies for stimulating language development, including vocabulary learning, as they involve memory, rhythm, motor activities, and emotionally engaging learning experiences. This study reviewed various national and international journal articles, books, and relevant research reports. A thematic analysis was employed to identify recurring patterns and key contributions from previous studies. The findings indicate that singing-based activities consistently enhance children’s ability to remember, pronounce, and use English vocabulary. Songs accompanied by physical movements strengthen memory retention through the integration of auditory, visual, and kinesthetic stimulation. Previous studies have reported significant improvements in children’s vocabulary acquisition after participating in song-based learning activities, highlighting the role of repetition, rhythm, and body movement in accelerating vocabulary internalization and increasing children’s confidence in communication. Furthermore, the use of singing and action songs creates a positive, focused, and enthusiastic learning atmosphere, allowing children to express themselves freely while strengthening emotional bonds between teachers and learners. Based on these findings, singing and action songs are recommended as effective and practical strategies for English vocabulary instruction in early childhood education. This literature study contributes both theoretically and practically by providing insights for educators in selecting creative and developmentally appropriate teaching methods.